2013
DOI: 10.1126/scitranslmed.3004438
|View full text |Cite
|
Sign up to set email alerts
|

Blocking NRG1 and Other Ligand-Mediated Her4 Signaling Enhances the Magnitude and Duration of the Chemotherapeutic Response of Non–Small Cell Lung Cancer

Abstract: Although standard chemotherapies are commonly used to treat most types of solid tumors, such treatment often results in inadequate response to, or relapse after, therapy. This is particularly relevant for lung cancer because most patients are diagnosed with advanced-stage disease and are treated with frontline chemotherapy. By studying the residual tumor cells that remain after chemotherapy in several in vivo non-small cell lung cancer models, we found that these cells have increased levels of human epidermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 44 publications
3
60
0
1
Order By: Relevance
“…Our laboratory found that primary NSCLCs contain a small subpopulation of NRG1 þ cells and that NRG1 and its receptors HER3 and HER4 are enriched in residual tumor cells that survive chemotherapy treatment. Moreover, inhibition of NRG1 signaling enhanced the magnitude and duration of the response to chemotherapy in several in vivo models (29). Recent studies highlight the impact of intratumoral heterogeneity in NRG1 and HER3 expression in breast cancer.…”
Section: Heterogeneity In Ligand/receptor Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory found that primary NSCLCs contain a small subpopulation of NRG1 þ cells and that NRG1 and its receptors HER3 and HER4 are enriched in residual tumor cells that survive chemotherapy treatment. Moreover, inhibition of NRG1 signaling enhanced the magnitude and duration of the response to chemotherapy in several in vivo models (29). Recent studies highlight the impact of intratumoral heterogeneity in NRG1 and HER3 expression in breast cancer.…”
Section: Heterogeneity In Ligand/receptor Expressionmentioning
confidence: 99%
“…Trials are currently under way to assess whether the endocrine therapy index of CTCs is correlated with patient outcome (28). Heterogeneous expression of the ERBB3 (HER3) and its ligand NRG1 have been reported in a variety of human cancers, including breast cancer, lung cancer, and glioblastoma (23,29,30). HER3 signals as heterodimer with other receptors of the HER family leading to potent activation of the PI3K/AKT pathway (22).…”
Section: Heterogeneity In Ligand/receptor Expressionmentioning
confidence: 99%
“…In addition to growth factor regulation of cell proliferation and differentiation, recent reports show an important role for multiple RTK ligands in resistance to kinase inhibitors (7)(8)(9). The HER3 ligand, neuregulin 1 (NRG-1), was recently shown to mediate resistance to chemotherapeutic agents as well (10). Moreover, HER3 was reported to mediate resistance to EGFR, HER2, and PI3K inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the mAbs show synergy with chemotherapy on lung cancer cells. 88 Notably, because NRG1 binds both HER3/ERBB3 and HER4/ERBB4, and the latter receptor is expressed in cardiac and neural tissues, toxicity might become an issue when targeting NRGs. Another way to target the ligands is a decoy receptor strategy.…”
Section: Her3 Strategies Involving Ligand Targetingmentioning
confidence: 99%
“…100 1) The ligand trapping strategy consists of developing recombinant decoys (aka TRAP). 89 or anti-NRG antibodies, 88 thereby avoiding ligand-induced activation of HER3. (2) Since HER3 homodimers are weakly active compared to the heterodimers HER3-HER2 and HER3-EGFR, a recombinant bivalent-NRG has been developed that locks HER3 in the homodimeric conformation and restricts its ability to form heterodimers.…”
Section: Others Indirect Strategiesmentioning
confidence: 99%